Immune Dysregulation in Childhood Leprosy - Flora Ramona Sigit Prakoeswa; Budi Prasetyo; Santi Martini; Hardyanto Soebono; Muhammad Yulianto Listiawan; Anang Endaryanto; Cita Rosita Sigit Prakoeswa (Institute of Medico-legal Publications Pvt Ltd, 2021)
Leprosy is a chronic infection which is caused by Mycobacterium leprae. Leprosy has long been considereda complex disease, in which host and environmental characteristics are as important as the pathogen todetermine disease outcome. Leprosy is an excellent model for examining the immunoregulatory functions.Children are believed to be the most vulnerable group to leprosy infection due to their immature immunity.This review is aimed to summarize the findings of previous studies about immune dysregulation in childhoodleprosy. This study highlighted the plausible maternal-fetal connection which are related in immunedysregulation in childhood leprosy.